Development of Monitoring Tool to Support Lean Manufacturing Implementation - Septi Ayu Angrayni; Putu Dana Karningsih (Institut Teknologi Sepuluh Nopember, 2020)
Lean is an approach that is carried out continuously to identify and eliminate waste or other activities that do not provide added value. Many companies have implemented lean concepts and got the benefits such as reduced cycle time, reduced operational costs, improved product quality, and other benefits. Although it provides many benefits, there are some weaknesses in implementing lean, one of which is due to the lack of monitoring. After the initial implementation, the process has never been reviewed and is rarely checked to ensure its implementation. Monitoring lean implementation requires tools that can help monitor work more efficiently. There are no specific tools that can be used to control and oversee lean implementation in the company. For this reason, this research will develop a tool for monitoring lean implementation. The tools to be developed adopting the logic of several methods, namely Quality Function Deployment (QFD), the framework of three matrix houses in lean implementation, and the House of Risk (HOR). This Lean monitoring tool is used to ensure that the corrective actions recommended for lean implementation are implemented. The Lean monitoring tool consists of three matrices that offer the ability to identify potential failures, the root causes of failures, and solutions to deal with lean implementation failuress.